Ruined or Accessible? TikTok and Stakeholder Narratives of the Kelingking Beach Elevator - Ni Kadek Swandewi; Nina Indra Kristiana; Fransiska Fila Hidayana; Leily Suci Rahmatin; I Gede Sumadi (Universitas Merdeka Malang, 2026)
Social media has become a crucial arena where such debates are produced and amplified. This study examines how the Kelingking Beach elevator project in Nusa Penida is constructed and contested through digital and local visual narratives. Using a qualitative-dominant design, the research combines TikTok netnography, manual stance coding, Multinomial Naive Bayes classification, and photo-elicitation interviews with five local stakeholders. TikTok comments were collected from one international and one national news account, cleaned, coded into pro-elevator, contra-elevator, and neutral or ambiguous categories, and transformed into TF-IDF features for classification. The results show that opposition dominates the online discourse: 513 comments were classified as contra, 122 as pro, and 39 as neutral or ambiguous. Contra narratives frame the elevator as environmental degradation, visual damage, overtourism, weak governance, and unequal tourism benefits. Supportive narratives, although smaller, emphasise accessibility, visitor safety, and modern tourism infrastructure. Photo-elicitation findings largely confirm these tensions, while adding place-based concerns about legality, investment certainty, local economic justice, and misplaced infrastructure priorities. The study concludes that the elevator is perceived less as a neutral access facility than as a symbolic arena where conflicting visions of sustainable tourism, social inclusion, and landscape protection in Bali are negotiated.